Bahasa dalam Media Sosial: Kajian Linguistik Digital terhadap Gaya Bahasa Generasi Milenial dan Gen Z - Anita Candra Dewi (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
The development of digital technology has changed the way of communicating, especially among Millennials and Gen Z. Social media has become the main medium of interaction that influences the structure and use of language. This study aims to examine the language style used by Millennials and Gen Z in social media and its contribution to language evolution. The method used is a literature study by analyzing research related to digital linguistics and online communication. The results of the study show that the language style in social media is concise, uses a lot of abbreviations, emoticons, mixed codes, and slang. In addition to being a means of communication, the use of language in social media reflects a dynamic social identity and digital culture. This phenomenon shows that social media plays a role in forming and spreading new language variations. This study provides insight into the dynamics of language change in the digital era and its implications for today's communication.